Cross-country analysis of faecal sludge dewatering. Issue 23 (2nd December 2018) - Gold, Moritz; Harada, Hidenori; Therrien, Jean-David; Nishida, Takahiro; Cunningham, Michael; Semiyaga, Swaib; Fujii, Shigeo; Dorea, Caetano; Nguyen, Viet-Anh; Strande, Linda
ABSTRACT: Dewatering of faecal sludge (FS) is indispensable for adequate FS management. However, comprehensive knowledge is lacking on FS dewatering performance. This study compared the dewatering performance of FS from different countries and onsite sanitation technologies, to assess influential characteristics on dewatering, and to compare dewatering performance of FS with wastewater sludge. We collected 73 FS samples from septic tanks, lined pit latrines, unlined pit latrines and johkasou tanks in Uganda, Vietnam and Japan, and 18 samples of wastewater sludge in Switzerland. Capillary suction time (CST) and total solids (TS) of centrifuged sludge (%TSfinal ) were determined as metrics of dewatering rate and dewaterability, respectively, together with relevant sludge characteristics. Data were analysed by bootstrapping comparison of median results of each sample category and by bootstrapping multiple regression analysis to quantify the relative importance of sludge characteristics on dewatering performance. Results showed that the dewatering rate was significantly different between FS from different technologies, whereas dewaterability was significantly different within the same technology. FS had a significantly lower dewatering rate than wastewater sludge. In contrast, FS dewaterability was greater than wastewater sludge. However, this could be attributed to higher concentrations of sand in FS. Electrochemical properties such as NH4 -N and surface charge had the strongest correlation to dewatering rate, and solid properties such as sand content and total volatile solids to dewaterability. The results identify potential characteristics that could explain and predict the high variability of FS dewatering performance that is observed in the field.